Correlation Between Oxidative Stress, SIRT1 Serum Level, and eGFR on Elderly - Harun, Harnavi; Veronike, Evelin; Kam, Alexander; Amelia, Rinita (Postgraduate, University of Mataram, 2023)
The aging network kidney causes Oxidative Stress (OS) and damages the kidney. Studies of aging kidneys keep going growing by developing sirtuin as an antiaging. Sirtuin 1 (SIRT1) is a protein implicated in several disorders including diabetes functions as an anti-aging protein. Decreased eGFR in the elderly caused by his height prevalence factor risk disease kidney at an older age. The study aims to study the correlation between oxidative stress, SIRT1 serum levels, and eGFR in the elderly. Â The method used in this research is observational with the cross-sectional method. The sample in this study was the whole elderly who met the inclusion and exclusion criteria, totaling 30 people. Exclusion criteria are patients with glomerulonephritis, nephropathy obstruction, nephropathy sour veins, and obesity. All patients complied requirements asked to fill informed consent form. The inspection was carried out by urinalysis ultrasound kidney and assessing serum MDA levels which were found to be higher in this study. This study showed SIRT1 and eGFR levels decreased in the elderly. There was a negative correlation with moderate correlation strength between serum MDA levels and serum SIRT1 levels and a strong correlation between serum MDA levels and eGFR in the elderly. There was a positive correlation with a moderate correlation between serum SIRT1 levels and eGFR in the elderly. SIRT1 is suggested to be examined in elderly patients with decreased eGFR, even without comorbidity.